Genetic diversity of hepatitis C virus and resistance associated substitutions to direct-acting antiviral treatment in Colombia (2022)
ABSTRACT: Hepatitis C virus (HCV) infection is one of the leading risk factors for end-stage liver disease development worldwide. This RNA virus displays high genetic diversity with 8 genotypes and 96 subgenotypes with heterogeneous geographical distribution around the world. In this study, we carried out an active case finding of individuals with a history of transfusion events before 1996 in three cities in Colombia. Then, the characterization of the HCV genotypes, subgenotypes, and resistance associate substitutions (RAS) was performed in samples positives for antibodies anti-HCV + from this study population. In addition, samples from PWID and patients with end-stage liver disease submitted to liver transplantation were included in the phylogenetic and RAS analysis. The 5'UTR, NS5A, and NS5B regions of the HCV genome were amplified in serum or liver explants samples. After the edition, assembly, and alignment of the sequences, genotyping through phylogenetic analysis was performed using IQTREE V2.0.5 based on the maximum likelihood approach. The identification of RAS was carried out by alignments based on the reference sequence (GenBank NC_004102). Two hundred sixty individuals with blood transfusion events before 1996 were recruited. The seroprevalence of antibodies anti-HCV was 2.69% in this population. The HCV genotypes 1, 2, and 4 and subgenotypes 1a, 1b, 2a, 4a and 4d were characterized in samples of the study populations. Three RAS (Q30R, C316N, and Y93H) were identified in samples obtained from 2 individuals who received blood transfusion before 1996 and without previous antiviral treatment and 6 samples obtained from patients with end-stage liver disease. Among the 20 samples analyzed, the HCV genotype 1, subgenotype 1b, was the most frequent (60%). We report the first characterization of HCV subgenotypes 4a and 4d and the first RAS identification in patients in Colombia. Keywords: Epidemiology; Evolution; Genetic diversity; Hepatitis C virus; Infection.